2006 IEEE Conference on Robotics, Automation and Mechatronics 2006
DOI: 10.1109/ramech.2006.252638
|View full text |Cite
|
Sign up to set email alerts
|

Active Vibration Suppression of a Flexible Link Using Ionic Polymer Metal Composite

Abstract: Polymers labeled as EAPs (Electro-active Polymer) have a mechanical response to electrical stimulation and produce an electric change in response to mechanical stimulation. The high strains of ionic polymer metal composite (IPMC) make them attractive as mechanical actuators for applications requiring large motion but little force. This paper describes the results an application of IPMC as active damper for a flexible link. IPMC is studied experimentally to find out material loss factors and damping characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…in active damping of structures, robotic grippers, structural health monitoring, flapping propellers, etc. [3,5,6,20]. The following conclusions are drawn from this analyses:…”
Section: Discussionmentioning
confidence: 70%
“…in active damping of structures, robotic grippers, structural health monitoring, flapping propellers, etc. [3,5,6,20]. The following conclusions are drawn from this analyses:…”
Section: Discussionmentioning
confidence: 70%
“…It is observed that two patches of IPMC have reduced the vibration around 75-85% quantitatively. A single loop PD controller has also been studied in (Bandopadhya, 2006). From sensor 1, and sensor 2, it is observed that in sensor 1, strain in terms of voltage is larger as the bending moment increases from tip of the rotating link toward the hub and reaches maximum at the hub.…”
Section: Resultsmentioning
confidence: 99%
“…They usually describe only the motion of the tip or the bending radius of the device assuming that the bending radius is constant. The equipment used to measure these parameters are for instance laser position sensors or force gauges (Jung et al, 2003;Richardson et al, 2003;Bandopadhya et al, 2006).…”
Section: Characterization Of the Actuatormentioning
confidence: 99%